A structural analysis of barriers in implementing marketing strategies in FMCG sector: empirical evidence from Pakistan - Basit, Abdul; Bhaumik, Amiya; Niazi, Abdul Aziz Khan (International Journal of Innovative Research and Scientific Studies, 2025)
Aim of the study is to analyze the underlying structure of barriers in implementing marketing strategies in the FMCG sector. The design of the study includes a review of literature, primary data collection, structural modeling, and analysis. Data are collected from a panel of experts recruited based on predetermined criteria. Literature discourse is adopted to identify an array of barriers, and Interpretive Structural Modeling (ISM) is employed as the modeling method. Additionally, scale-centric and data-centric cross-impact matrix multiplication applied to classification (MICMAC) is used as the analytical technique. The literature review revealed a total of sixteen barriers in implementing marketing strategies in the FMCG sector. The ISM modeling results indicated that lack of knowledge and skills occupy Level III (bottom), while lack of systematic approach, product innovation, and integrated marketing communication occupy Level II (middle). All other barriers are positioned at Level I (top). The MICMAC analysis, both scale-centric and data-centric, corroborates the findings of the ISM modeling. This study is valuable for marketers, FMCG company management, regulators, researchers, and customers, as it provides an understanding of the underlying structures and relationships among the barriers in implementing marketing strategies in the FMCG sector. It contributes a list of barriers, a structural model, and scale- and data-centric driving-dependence diagrams to the existing literature, offering new insights subject to certain limitations inherent in qualitative research.